Partisipasi Masyarakat dan Mekanisme Komplain dalam Penyelenggaraan Pelayanan Publik - Tovalini, Krismena (Jurnal Ilmu Administrasi Negara (JUAN), 2014)
This paper describes the importance of public participation and complaint mechanism in the public servicedelivery. Society can participate in public service on three aspects: (1) community participation inplanning public services, (2) community participation in organizing special service, (3) communityparticipation in overseeing the public service. In addition, people can also make complaints on the publicservice to internal and external agencies. One of the external agencies that are expected to organizecomplaint is ombudsman. Ombudsman should be able to ensure that complaints submitted by the communityfollowed by public service providers.